Digital Grassroots Movements Within the Elderly: Case study analysis of online social protests in Spain about a retirement pay reform - Martinho Almagro, Teresa; Smolak Lozano, Emilia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The digitization of the public sphere has led to a greater visibility of collective citizen action and its participation as a political and social actor. The objective of this study focuses on the analysis of the digital citizen activism platforms of the retirement' associations movement in Spain through its social networks and platforms, with a case study of its main associations (COESPE and MERP) and its video content. The results extracted bring us closer to conceiving them as grassroots from their bases in the defense of their demands and visual identity of their main political and social actors.